A qualitative study of the role of Australian general practitioners in the surgical management of obesity. Issue 4 (20th April 2017) - Jose, K.; Venn, A.; Nelson, M.; Howes, F.; Wilkinson, S.; Ezzy, D.
Summary: General practitioners (GPs) are increasingly managing patients with class 2 and 3 obesity (body mass index [BMI] > 35 and 40 kg/m 2, respectively). Bariatric surgery is considered for patients with class 2 obesity and comorbidities or class 3 obesity where sustained weight loss using non‐surgical interventions has not been achieved. In Australia, GPs facilitate access to surgery through referral processes, but the nature of GP involvement in bariatric pre‐ and post‐surgery care is currently unclear. This qualitative study involved 10 in‐depth interviews with GPs and 20 interviews with adults who had all undergone laparoscopic adjustable gastric banding (LAGB) for weight management in Tasmania, Australia. Interviews were transcribed and analysed thematically. Referrals for bariatric surgery commonly occurred at the patient's request or to manage comorbidity. Consistent with previous studies, for GPs, referral patterns were influenced by previous case experience and patients' financial considerations. Accessibility of surgery was also a consideration. Post‐surgery, there was a lack of clarity about the role of GPs, with patients generally preferring the surgical team to manage the LAGB. In bariatric surgery, patient preference for surgery, access and comorbidity are key drivers for referral and post‐surgical monitoring and support. Greater role clarity and enhanced collaboration between surgeons, GPs and patients following surgery is likely to enhance the experience and outcomes for patients.